Fiber in-line Mach-Zehnder interferometer for simultaneous measurement of transverse loading and temperature based on multi-core fiber. (November 2021) - Li, Yichun; Song, Zhuo; Wei, Jinpeng; Hu, Junhui
Highlights: The proposed sensor has the potential to measure temperature and transverse pressure simultaneously. The obtained transverse pressure and temperature sensitivities can reach up to −165 pm/N and 45 pm/°C, respectively. The proposed sensor has the advantages of easy fabrication, simple structure, high sensitivity, and cost-efficient. Abstract: A fiber in-line Mach-Zehnder interferometer (MZI) is proposed and experimentally demonstrated for simultaneously measuring transverse loading and temperature. The MZI is fabricated by simply splicing a segment multicore fiber (MCF) with two short sections of multimode fibers (MMFs). The sensing principle is theoretically analyzed and the transverse loading and temperature characteristics of the sensor are investigated in experiment. The results show that the multimode interference among the center core mode (CCM), the cladding modes (CM) and outer core mode (OCM) of the MCF enables the sensor to realize the measurements of transverse loading and temperature. The transmission spectra will shift when the external transverse loading and temperature variation, and different spectral responses of the resonant dips are observed, which indicates that the sensor can implement the simultaneous transverse loading and temperature measurement by monitoring the wavelength changes of two resonant dips. The obtained sensitivities of transverse pressure and temperature can reach up to −165 pm/N and 45 pm/°C, respectively. The proposed sensor has the potential application in the fields where both temperature and transverse loading measurements are required.